2019
DOI: 10.1080/07366299.2019.1691300
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Two-Phase Flow in a Hybrid Pulsed Sieve-Plate Solvent Extraction Column: Prediction of Holdup and Axial-dispersion Coefficients

Abstract: Two-phase computational fluid dynamics (CFD) models for a hybrid pulsed sieve plate solvent extraction column as well as a standard pulsed sieve plate column have been developed with commercial software ANSYS FLUENT. Hydrodynamic performance including two-phase distribution and velocity fields are generated with the models and comparisons are made between two columns. Important parameters including holdup and axial dispersion coefficients are studied systematically, and CFD successfully predicts the higher hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, several studies have shown that the use of PBM cannot provide a correct prediction of the holdup under high pulsation intensities. 17,18 This implies that d 32 introduces uncertainties and causes significant errors at high pulsation. The basic cause is the d* does not meet the requirement of d 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that the use of PBM cannot provide a correct prediction of the holdup under high pulsation intensities. 17,18 This implies that d 32 introduces uncertainties and causes significant errors at high pulsation. The basic cause is the d* does not meet the requirement of d 32 .…”
Section: Introductionmentioning
confidence: 99%
“…It determines the number densities of different droplet sizes and provides d 32 as the interface area for the CFD solver. However, several studies have shown that the use of PBM cannot provide a correct prediction of the holdup under high pulsation intensities 17,18 . This implies that d 32 introduces uncertainties and causes significant errors at high pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…Sen et al 27 reported a CFD-PB model that can be used to numerically estimate the continuous phase axial dispersion coefficient in two-phase flow. Yi et al 28 reported a two-phase CFD model to predict the drop size and axial dispersion coefficient in hybrid pulsed sieve plate columns. However, in all of these attempts, validation of CFD models is carried out by comparing predicted macroscopic variables like holdup or droplet diameter against experimentally measured values.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Pulsed extraction columns have been widely used because of their many advantages, such as a small footprint, large processing flux, no rotating internal parts, and the ability to handle materials containing solid particles. 18 Because the interfacial tension is a key physical property in multiphase flow, 19 it is important for predicting hydraulic properties, such as the Sauter mean diameter (SMD) of liquid droplets, 20 flooding characteristics, 21 and dispersed phase holdup 22 in pulsed extraction columns. Studies have shown that under masstransfer conditions, dynamic changes in the interfacial tension occur, resulting in changes in the hydraulic behavior of the extraction devices.…”
mentioning
confidence: 99%